The Third Body Effect of Carbon Dioxide on N-heptane Ignition Delay Characteristics under O2/CO2 Conditions. Issue 14 (26th October 2022) - Liu, Yongfeng; Sheng, Yuqi; Wei, Ping; Zhang, Lu; Yao, Shengzhuo; Liu, Haifeng; Sun, Hua
ABSTRACT: In order to study the impact of CO2 during n-heptane ignition delay under O2 /CO2 conditions, this study presents a numerical and experimental study in four cases (40 mol.% O2 /60 mol.% CO2, 50 mol.% O2 /50 mol.% CO2, 57 mol.% O2 /43 mol.% CO2 and 65 mol.% O2 /35 mol.% CO2 ). Firstly, a third body effect (TBE) model is presented, which considers the third body efficiency of CO2 . Secondly, the TBE model adds the third body efficiency into a one-step global mechanism and obtains an ignition delay time formula according to the auto-ignition theory. Thirdly, experiments are carried out in a constant volume combustion chamber (CVCC) test system. Furthermore, the experiment and simulation results are compared and discussed. In addition, two parameters (α and β) are defined to study the third body effect and the chemical effect of CO2 respectively. Finally, chemical kinetic analyses are used to study the CO2 effect. The results show that the TBE model is in agreement with the experiment and the maximum difference is 8.94% under the 57 mol.% O2 /43 mol.% CO2 condition. The third body effect is the main effect of CO2 and it can decrease small molecule intermediates and radicals. Besides, C3 H6 O is the most affected species by the third body effect of CO2 among four prominent intermediate species. Furthermore, the third body effect of CO2 inhibits most paths of OH production. H+ O2 →O+ OH (R11) is the most affected pathway whose peak rate of production (ROP) decreases by 51.5%.